Hidden in the bushes: uncovering the diversity of the genus Neometrypus Desutter, 1988 n. status (Orthoptera: Gryllidae: Paroecanthini: Tafaliscina) in Neotropical forests - de Campos, Lucas Denadai; Souza-Dias, Pedro G. B. (Zootaxa, 2021)
Neometrypus Desutter, 1988 n. status is elevated to the generic level. Ten new species of this genus are described (N. azevedoi n. sp., N. carvalhoi n. sp., N. catiae n. sp., N. couriae n. sp., N. lopesae n. sp., N. maiae n. sp., N. marcelae n. sp., N. mejdalanii n. sp., N. mendoncae n. sp., N. monnei n. sp.). All the species are from Brazil, nine from the Atlantic Forest, and one from Amazonia. We also provide a distribution map of all type localities of Neometrypus n. status, an identification key for all 13 known species of the genus, the first record of the mating behavior, and a short discussion about paedomorphic characters and communication between these crickets.